IMPROVEMENT STRATEGY FOR CREATING VALUE IN INCLUSIVE BUSINESS PLATFORM (KUKM ECOBIZ) FOR ENHANCING USER ACTIVITY (The Indonesian Journal of Business Administration, 2019)
KUKM Ecobiz is a collaborative platform between DEKOPINWIL West Java and an expertise team from SBM ITB supported to provide a digital platform from DEKOPINWIL and business supporters specifically cooperatives, SMEs, livestock, farmers, the government, and associations to exchange information about improving shared economy. Marketing efforts have been carried out on several cooperatives through training for several cooperatives in West Java through DEKOPINWIL, but the activity on the platform is still low. The objective of this study is to improve the competence and capabilities of cooperative members, SMEs, as well as farmers and livestock, review UI and UX, recommend website development based on user preferences, and finally increase activities in the KUKM Ecobiz platform. The data collection methodology used in this study mostly uses qualitative data. The primary data came from the previous research questionnaire and the questionnaire. For secondary data obtained from the Ecobiz KUKM database, several websites, and several sources that can support this research. Several stages of analysis are carried out, the first being external analysis using PEST analysis and other similar platform analysis. For internal analysis using platform analysis, comparing with good UI and UX methods, and using platform user needs analysis. After that, to proceed to the solution, it is necessary to search for the root of the problem using CRT (Current Reality Tree). To gain user activity, KUKM Ecobiz needs to do several scenarios that are intended to trigger activities in Ecobiz KUKM such as requiring chosen cooperative members to interact in the forum and several other things. Then create content that suits the needs of KUKM Ecobiz users, and design the KUKM Ecobiz website again with the rules of designing existing software.Keywords:  Inclusive Business, Digital Platform, KUKM Ecobiz, Network Effect, CRT, User Experience.